2016
DOI: 10.1556/2006.5.2016.029
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Impulsivity in Obsessive–Compulsive Disorder

Abstract: BackgroundGrassi et al. (2015) collected data to examine impulsivity in individuals with obsessive–compulsive disorder (OCD) compared to nonpsychiatric controls. Their aim was to examine whether OCD may be fully captured by the behavioral addiction model, using the prototypical mechanism underlying drug addiction as their framework. Based on their findings, Grassi et al. concluded that OCD shares behavioral components with addictions, particularly behavioral impulsivity and risky decision making. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
3
17
1
Order By: Relevance
“…OCD patients here, despite being largely free of any comorbidities, had significantly higher BIS attention-related impulsivity, consistent with previous findings [22,23,57]. Nevertheless, there was no evidence of a JTC reasoning style, or any association between impulsivity and task performance.…”
Section: Discussionsupporting
confidence: 90%
“…OCD patients here, despite being largely free of any comorbidities, had significantly higher BIS attention-related impulsivity, consistent with previous findings [22,23,57]. Nevertheless, there was no evidence of a JTC reasoning style, or any association between impulsivity and task performance.…”
Section: Discussionsupporting
confidence: 90%
“…At the end of treatment then, upon completion of an intensive multimodal outpatient treatment protocol, these more significantly impaired comorbid children who had poorer treatment outcomes were also the patients still exhibiting secondary symptoms such as inattention, impulsivity, etc. The finding that hyperactivity-impulsivity was correlated with obsessions and compulsions at the end of treatment comes in contrast with many studies that have shown that adults with OCD are generally less impulsive than healthy controls (Abramovitch & McKay, 2016). Children with OCD may present with different challenges, as agitation from chronic obsessional distress may contribute to related problems like emotional dysregulation (McGuire et al, 2013; McNamara et al, 2014) and oppositionality (Lebowitz, Omer, & Leckman, 2011) which can also contribute to secondary symptoms like hyperactivity and impulsivity.…”
Section: Discussioncontrasting
confidence: 61%
“…Indeed, Abramovitch and colleagues (2012; Abramovitch, Dar, Mittelman, & Schweiger 2013) found that while obsessions and compulsions may be linked with ADHD symptoms and executive dysfunction among individuals with OCD, the two constructs seem to be unrelated in people with subclinical levels of obsessive-compulsive symptoms. Finally, numerous studies have demonstrated that adults with OCD are less behaviorally impulsive than healthy controls (Abramovitch & McKay, 2016), though these results have not been replicated with children and adolescents. The frequency of hyperactive-impulsive symptoms in children with OCD may be different; obsessive-compulsive symptom severity has been linked with other externalizing behaviors like oppositionality and defiance (Lebowitz, Omer, and Leckman, 2011) and emotional dysregulation (McGuire et al, 2013; McNamara et al, 2014), which may in turn be associated with impulsive, hyperactive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Abramovitch and McKay (2016) argued that higher scores on the BIS-11 cognitive subscales in our OCD group could be simply explained by excessive doubting, and therefore contradict the behavioral addiction model of OCD. However, we also found increased cognitive impulsivity on the Beads Task, which could not be explained by excessive doubting as patients accumulated significantly fewer evidence prior to decision than controls, reflecting overconfidence rather than excessive doubting.…”
mentioning
confidence: 73%
“…Abramovitch and McKay (2016) argued that this conclusion is untenable by suggesting that (a) our finding of increased cognitive impulsivity and non-planning impulsivity on the Barratt impulsiveness scale (BIS-11) in OCD patients may support cognitive impulsivity, but not behavioral impulsivity that is typical for addiction and (b) risky decision-making on the Iowa gambling task (IGT) and fewer draws to decision on the Beads Task in our OCD patients may be accounted for by doubting and risk avoidance, rather than the typical risk-taking behaviors of addiction.…”
mentioning
confidence: 99%